Region-based group and hierarchical key management for secure smart grid communications. (2016) - Viswanatham, V. Madhu; Chari, A.A.; Saritha, V.
Considering the security requirements of smart grid in modern environment where they are used in cities, states and countries it has become imperative to develop a region-based security protocol for them. To provide security to group-based applications, the group members need to have a secret key which is common to all. The task of providing security to the group applications is a very critical task in smart grid. Considering this challenge for secure group applications, we propose a region-based group and hierarchical key management protocol. The protocol becomes scalable and reconfigurable dynamically by grouping the smart meters which behave as nodes in the smart grid based on the range of distribution substation (DSS). These TUs are hierarchically divided into different DSSs. The number of times the packet is encrypted is based on the number of levels in the hierarchy. As the levels in the hierarchy increases, the security is increased but the complexity also increases. The proposed protocol proves to be good, typically adapted to mobility of nodes and the performance of the protocol shows significant results.